Class III treatment using facial mask: Stability after 10 years - Adilson Luiz Ramos (Dental Press Editora, 2014)
Early Class III malocclusion treatment may not have long-term stability due to mandibular growth. Although some features of this malocclusion point to a better prognosis, it is practically impossible for the orthodontist to foresee cases that require new intervention. Many patients need retreatment, whether compensatory or orthodontic-surgical. The present study reports the case of a Class III patient treated at the end of the mixed dentition with the use of a face mask followed by conventional fixed appliances. The case remains stable 10 years after treatment completion. It was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as a requirement for the title of certified by the BBO.